Irrigation and organic fertilization on the production of essential oil and flavonoid in chamomile - Catariny C. Aleman; Patricia A. A. Marques (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The therapeutic efficacy of herbal medicines and pesticides has increased the need to define cultivation parameters for medicinal plants. The objective of this study was to evaluate the production of essential oil and flavonoids of chamomile under irrigation levels and organic fertilizer doses. The experiment was conducted in the experimental area of the Campus II of the University of Western São Paulo, in the city of Presidente Prudente, SP, Brazil. The experimental design was a randomized block in triple factorial (6 x 2 x 3), corresponding to irrigation depths (150, 100, 75, 50, 25 and 0% of the reference evapotranspiration (ETo)), organic fertilizers (poultry manure and cattle manure) and the fertilizer doses (0, 3 and 5 kg m-2), with four replicates. The following variables were evaluated: capitulum dry matter, and content and yield of essential oil and flavonoids. For the tested conditions, it is recommended to use 5 kg m-2 poultry manure and water depth equivalent to 150% ETo for the production of essential oil and flavonoid.